Evaluasi Tingkat Kesulitan Mahasiswa Universitas Stella Maris Sumba dalam Memahami Teknologi Informasi - Lukas Dairo Ngadu; Ardiyanto Dapadeda; Emirensiana Dappa Ege (Jurnal Publikasi Teknik Informatika, 2026)
The growth of information technology (IT) has become a significant foundation in the world of learning, especially in higher education. IT mastery skills are not only needed to support the educational process, but also to prepare students to face the demands of the world of work. Identifying how students understand information technology. Identifying factors that influence students' difficulties. Providing solution recommendations to improve students' understanding of Information Technology (IT). This study uses a descriptive qualitative approach. This approach was chosen because it aims to describe in depth the phenomena experienced by students, especially related to difficulties in understanding information technology. Data were collected through questionnaires and analyzed using descriptive statistical techniques. This shows that the level of students' understanding of information technology such as; reactions (74.2%) is the most dominant factor, while learning (70.6%) and results show (67.3%) then the level of students' understanding of information technology (67.3) so that there are still obstacles to students' understanding of information technology. need to improve the quality and learners related to the level of student understanding.